Risiko Harga Cabai Pada Tingkat Petani di Kabupaten Kediri - Zakkiya, Niken Hefa; Rizkiyah, Noor; Barokah, Umi (Gorontalo State University, 2026)
Unstable chili prices are often caused by external factors such as weather conditions, harvest seasons, and unpredictable market dynamics. This study uses weekly chili price data for two years obtained from the Strategic Food Price Information Center (PIHPS-BI), the data was analyzed using the Coefficient of Variation (KV) and ANOVA (Analysis of Variance) methods. This study has purpose to analyze price risks for various chili varieties cultivated by farmers in Kediri Regency. The conclusions obtained in this study are (1) red chili, large red chili, and curly red chili have a high price risk with a coefficient of variation (KV) value of 0.5 while green cayenne pepper shows a lower price risk with a coefficient of variation (KV) value of 0.5 which tends to be more stable, (2) The ANOVA test produces a significance value of 0.000 ( 0.05), which indicates a significant difference in price risk between chili varieties in Kediri Regency.